WORK-FAMILY BALANCE AND JOB ATTITUDES IN UVWIE AND UDU LOCAL GOVERNMENT AREAS OF DELTA STATE, NIGERIA - Lovetha Okeoghene Azuike; Akpomuvire Mukoro (Malikussaleh Social and Political Reviews, 2025)
This study aims to examine the impact of work-family balance on work attitudes, particularly job satisfaction, organizational commitment, and work engagement, among employees in Uvwie and Udu Local Government Areas of Delta State. The study adopted a cross-sectional research approach, utilizing structured questionnaires to collect data from 440 respondents across various organizations and was anchored on conservation of resources theory. The findings revealed that work-family balance positively and significantly influences job satisfaction, organizational commitment and job involvement among employees in Uvwie and Udu Local Government Areas of Delta State. The findings underscore the importance of work-family balance initiatives in enhancing employee well-being and organizational effectiveness. The study concluded that ensuring work-family balance is not only beneficial to employees but also serves as a strategic advantage for organizations striving for sustainable growth and productivity. The study recommended among others that Uvwie and Udu Local Government Areas of Delta State should adopt flexible work policies such as remote work options, compressed workweeks, and flexible working hours. These policies will enable employees to better balance their work and family responsibilities, leading to increased job satisfaction and overall well-being. This study contributes to the growing body of knowledge on work-family balance and provides practical insights for organizations aiming to enhance employee job attitudes and overall productivity.